2020
DOI: 10.1080/08990220.2020.1765767
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sensory stimulation applied under the great toe on postural ability in patients with fibromyalgia

Abstract: Fibromyalgia (FM) is a chronic pain syndrome, characterised by several symptoms. One of the most prevalent symptoms in FM is balance impairment that compromise the autonomy, function and per-formance status of patients. Purpose: The main objective of the present study was to evaluate the effect of sensory stimulation provided by the use of a low additional thickness of 0.8 mm placed under the great toes bilaterally on the centre of pressure (CoP) measures in patients with FM. It was hypothesised that postural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 67 publications
1
6
0
Order By: Relevance
“…This result means that the center of pressure (COP) trajectory covers a larger area in this population in single-leg standing and it is consistent with the results of a previous study conducted in subjects with fibromyalgia who reported a similar increase in the area in a bipedal test with eyes open [42]. The tendency for the linear values of COP, sway area, and range of the COP to increase in FMS can be attributed to chronic pain experienced by this population [43]; it is possible that the motor pattern adapts to this condition and therefore modifies movement and stiffness to protect against further pain [44]. Previous studies in which pain was experimentally induced have reported a larger area [45].…”
Section: Discussionsupporting
confidence: 91%
“…This result means that the center of pressure (COP) trajectory covers a larger area in this population in single-leg standing and it is consistent with the results of a previous study conducted in subjects with fibromyalgia who reported a similar increase in the area in a bipedal test with eyes open [42]. The tendency for the linear values of COP, sway area, and range of the COP to increase in FMS can be attributed to chronic pain experienced by this population [43]; it is possible that the motor pattern adapts to this condition and therefore modifies movement and stiffness to protect against further pain [44]. Previous studies in which pain was experimentally induced have reported a larger area [45].…”
Section: Discussionsupporting
confidence: 91%
“…However, while in patients with low back pain, the dry needling in painful areas and penetrating all the muscle groups show to have an improvement of pain and an increase in static postural control immediately (Brumagne et al, 2008), the effects of the FDB muscle dry needling, looking at our study results, in the foot differ in relation to the balance. & Sinnott, 1973), and in different diseases with different areas of MTrP as fibromyalgia (Viseux et al, 2020). In this sense, it is logical that the reduction in local and referred pain that occurs after dry needling generates better balance processing by the central nervous system.…”
Section: Discussionmentioning
confidence: 99%
“…Proprioceptive fiber compression of MTrP, but not in other areas, has been shown to increase the pain threshold to pressure and referred pain, confirming its involvement in the pathophysiology of pain and involvement of proprioceptive fibers in this peripheral sensitization (Wang et al, 2010 ). Trigger points (MTrP) in the muscles of the neck have been associated with alteration in static postural control (Talebian et al, 2012 ), and subjects with fibromyalgia also show a deficit in balance (Viseux et al, 2020 ). Research investigating the effects of dry needling therapy has shown the ability to reverse the central sensitization process due to MTrP (Freeman et al, 2009 ; Giamberardino, 2003 ) In addition to being an effective therapy in treating pain, it is considered a safe technique (Fogelman & Kent, 2015 ; Kietrys et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…In response to this sensory feedback, corrective postural responses are evoked by lower limb neuromuscular system (Saeki et al, 2015;Tosovic et al, 2012). Some studies have highlighted the importance of peripheral sensory feedback applied to the plantar sole (Viseux et al, 2018(Viseux et al, , 2019Viseux, Martins, et al, 2020) and have improved clinical symptoms in Parkinsonian patients, including reduction in postural instability, through plantar sole stimulation (Brognara & Cauli, 2020;Viseux, Delval, et al, 2020). Given the linear relationship between the intensity of perceived pain and postural instability characterized by the velocity and amplitude of the centre of pressure displacement (Lihavainen et al, 2010;Ruhe et al, 2011Ruhe et al, , 2013Viseux et al, 2022), these results provide new clinical perspectives in the development of intervention strategies to manage postural instability and pain in patients with PD.…”
Section: Pharmacological Approachesmentioning
confidence: 99%